1997
DOI: 10.1523/jneurosci.17-08-02813.1997
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of K+Uptake in Glia Prevents Long-Term Depression Maintenance and Causes Epileptiform Activity

Abstract: Extracellular cesium causes synchronous, interictal-like bursting and prevents maintenance of long-term depression (LTD) in the CA1 hippocampal region. We have investigated the cellular mechanisms underlying cesium actions. Whole-cell recordings showed that brief (2 min) bath exposures to cesium caused pyramidal cell hyperpolarization associated with decreased membrane conductance attributable to blockade of an inward h-type current. After prolonged (Ͼ2 min) exposures, a late depolarizing response was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
112
2
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 50 publications
9
112
2
2
Order By: Relevance
“…Hippocampal slices were prepared from 18-to 25-d-old male Wistar rats (Janigro et al, 1997a). Briefly, halothaneanesthetized rats were decapitated, and the heads were kept in ice-cold, oxygenated-modified artificial CSF composed of (in mM): 120 NaCl, 3.1 KCl, 4 MgCl 2 , 1 CaCl 2 , 1.25 KH 2 PO 4 , 26 NaHC0 3 , and 10 dextrose.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hippocampal slices were prepared from 18-to 25-d-old male Wistar rats (Janigro et al, 1997a). Briefly, halothaneanesthetized rats were decapitated, and the heads were kept in ice-cold, oxygenated-modified artificial CSF composed of (in mM): 120 NaCl, 3.1 KCl, 4 MgCl 2 , 1 CaCl 2 , 1.25 KH 2 PO 4 , 26 NaHC0 3 , and 10 dextrose.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments performed to elucidate the electrical behavior of in situ glial cells were performed with either a wholecell patch or perforated patch technique (Janigro et al, 1997a) from visually identified cells in the stratum radiatum of the hippocampal CA1 and CA3 regions. Astrocytes were initially identified morphologically based on the characteristic size and shape of their soma; this identification was f urther confirmed by histochemical analysis on biocytin-filled cells (R. D'Ambrosio, G. M. McK hann II, and D. Janigro, unpublished results).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the h current (Ih) has been investigated (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and the following characteristics of Ih were reported: (a) Ih is a voltage-gated nonselective cationic conductance activated by membrane hyperpolarization, not by depolarization (8,14); (b) Ih is blocked by cesium chloride (CsCl) or 4-ethylphenylamino-1,2-dimethyl-6-methylaminopyrimidinium chloride (ZD7288) instead of tetrodotoxin (8,13,15); and (c) Ih channels occur in higher density in the apical dendrites than in the soma (8,14). In spite of many in vitro reports on Ih channels (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) as well as in vivo studies on the pacemaking function of Ih (25)(26)(27)(28), any contributions of Ih to epileptic activity are unknown in vivo, except for the one that showed the...…”
mentioning
confidence: 99%
“…In spite of many in vitro reports on Ih channels (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) as well as in vivo studies on the pacemaking function of Ih (25)(26)(27)(28), any contributions of Ih to epileptic activity are unknown in vivo, except for the one that showed the long-lasting enhancement of the widely expressed intrinsic Ih that converts the potentiated synaptic inhibition to hyperexcitability in the hippocampus of rats that had febrile seizures (29).…”
mentioning
confidence: 99%